HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATA DIKLAT MENGIDENTIFIKASI ILMU BANGUNAN GEDUNG SISWA KELAS X SMK N 1 PARIAMAN - 356-365 , Abrar Medi (CIVED, 2014)
ABSTRACT   This descriptive research is purposed to find out the relationship between learning motivation and learning outcomes for identifying construction lesson in class X SMKN 1 Pariaman. Population of this research is students of class X construction technique who are learning a subject matter of identifying building construction in their first semester, year of study 2013/2014. Samples are taken by “random sampling” technique. Instrument that is used in this research is questionnaire with Likert scale and data is analyzed by (1) descriptive analysis, (2) analysis requirement tests, that are normal test and linearity test, and (3) hypothesis tests consist of correlation test and signification test. From the results show that there is significant relationship between learning motivation and learning outcomes for students of X class construction technique SMKN 1 Pariaman, with level of confidence 95%. This can be seen in correlation test result that is rhit  0.860 ≥ rtable  0.294, and from t test result that is thit  11.05 ≥ ttable  2.021. Based on results, it can be concluded that the higher learning motivation of student, the better result of student’s learning outcomes.       Keyword: Learning Motivation, Learning Outcomes.